The Levels of Modern Standard Arabic in Egypt and its Role in Arabic Language Teaching for Indonesian - Nur Hidayatun Na'imah; Mirwan Ahmad Taufiq; Kholifiatul Masito (Journal of Arabic Language Studies and Teaching, 2022)
This study aims to reveal the importance of knowing the five levels of Modern Standard Arabic in Egypt. This study used a qualitative method with literature study through book references, dictionaries, and journals. The main object of this study is the Arabic language itself and its role in Arabic language teaching for Indonesian. The data were collected through interviews and documentation from some students in State Islamic University Sunan Ampel in Surabaya and Al-Azhar University in Cairo to get data from the reality. Then, the result of this study revealed that the level of Modern Standard Arabic in Egypt is important to know for Indonesian Arabic language learners in order to understand many forms of language in various situations and conditions as well as the existing kinds of literature such as in scientific forums up to daily conversations because it can represent the varieties of Arabic existing in other countries and to add the knowledge of Arabic literature by learning about colloquial language and linguistic phenomenon about it in Arabic teaching.    هدف هذا البحث إلى معرفة خمس مستويات اللغة العربية المعاصرة. تناول هذا البحث المنهج الكيفي بجمع البيانات حول الكتب والمعاجم والبحوث. وتركيز محور الدراسة هو اللغة العربية نفسها ودورها في تعليم اللغة العربية مع الظواهر اللغوية، والمحور الثاني هو الظواهر اللغوية التي تسبب هذه المستويات، طريقة جمع البيانات هي المقابلة مع بعض الطلاب الإندونيسيين بجامعة سونن أمبيل الإسلامية الحكومية سورابايا وجامعة الأزهر الإسلامية بالقاهرة. فنتائج الدراسة هي أن معرفة تقسيم اللغة العربية إلى خمسة مستويات مهمة لتساعد الإندونيسيين في فهم عدة صيغ من اللغة العربية إما الفصحى والعامية وتزويد المعلومات عن الثقافة العربية بتعيين العامية في تعليم اللغة العربية مع الاهتمام إلى الظواهر اللغوية تتعلق بهذه اللغة.